Confluence of Challenges: Massive Tubercular Pericardial Effusion Entangled with Heart Failure and Diabetes Mellitus - A Multidisciplinary Odyssey - Mohammad Abdul Motalib; Md Zulfikar Ali; Md Raisul Islam; Sagar Ahammed (KYAMC Journal, 2024)
This case report describes a rare and compelling presentation of Massive Tubercular Pericardial Effusion (MTPE) concomitant with Heart Failure (HF) and Diabetes Mellitus (DM). Tuberculosis, once thought to be a disease of the past, continues to manifest in diverse clinical scenarios, emphasizing the importance of maintaining a high index of suspicion, particularly in endemic regions. The patient, a 60-year-old male with a known history of DM and HF, presented with symptoms of worsening dyspnea, fatigue, and peripheral edema. A diagnostic workup revealed a massive pericardial effusion with characteristics suggestive of tubercular etiology, subsequently confirmed by pericardial fluid analysis. The challenges in managing this triad of conditions: MTPE, HF, and DM were addressed through a multidisciplinary approach involving cardiology, infectious disease, and endocrinology specialists. This case underscores the significance of a comprehensive diagnostic evaluation and collaborative management in optimizing outcomes for patients with complex cardiovascular and infectious comorbidities. KYAMC Journal Volume: 15, No: 01, April 2024: 56-58.